Speaker recognition based on auditory impression: The role of familiarity with the speaker and language - Šešum Mia; Drljan Bojana; Ivanović Maja; Arsenić Ivana (NBP: Nauka, bezbednost, policija)
Speech is a fundamental means of interpersonal communication. Speaker identification based on voice and speech can be analysed through two perspectives, expert listening by trained phoneticians, for the purpose of forensic speaker identification, and by naive listeners. Factors related to the success of identification often include prior familiarity with the speaker and the language they speak. The aim of the study is to examine whether speaker recognition based on auditory impressions is influenced by prior familiarity with the speaker and the language being spoken. A total of 218 female students from the Faculty of Special Education and Rehabilitation participated in the experiment. An instrument was specially designed for the purposes of this research. The results indicated that familiarity with the spoken language did not influence speaker recognition. Similarly, familiarity with the speaker had no significant effect on recognition, except in the case of the English-speaking speaker, whose voice and speech were more accurately recognized by participants who had been previously familiar with her. Given that the research findings did not consistently support the hypothesis regarding the connection between prior familiarity with the speaker and the language they speak and the success of speaker identification, it is necessary for future research to focus on examining the connection between recognizing speakers and the acoustic characteristics of their voice and speech.